PUBLIC AFFAIRS DIVISION END OF 19950700 (Tufts Archival Research Center, 2007)
Draft; Marginalia; Illegible/Difficult to Read; Budget for the public affairs division of the Tobacco Institute as of the end of July 1995. Includes the account, the 1995 budget and the estimated and requested amounts for 1996.